Peran Wanita Penjual Ikan Dalam Menunjang Ekonomi Rumah Tangga Di Kelurahan Kotandora Kecamatan Borong Kabupaten Manggarai Timur - Anita; Syamsuryati Habibah R. Darusman (Program Studi Pendidikan Ekonomi, Universitas Flores, 2017)
This research has a purpose to know the cause of woman in urban village Kotandora willing to work as fish seller and impact of mother housewife role become woman fish seller in Kelurahan Kotandora. The approach in is this research is qualitative approach. Data collection techniquees obtained by doing observations (observation), interviews, library study, and documentation. the results of the study generally indicate that the factors causing women in the Kelurahan Kotandora choose to work as a fish seller for economic reasons. This is because the saurce of income of husband in the family is relatively small, so unable to meet the needs of the household economy. Therefore there was an impact of the shift from the role of housewife to woman fishmonger.